Revitalization of Traditional Markets with the Concept of VRIO, Heritage Tourism, and Technology to Strengthen Existence in the Era of Society 5.0 - Khakim, M. Azizul (Jurnal Ekonomi, 2024)
Society 5.0 has currently shifted many things in community life. This research focuses on the mission of considering and formulating strategies to be implemented by traditional markets in order to maintain their existence in this era. Researchers have considered that the concept of VRIO (Variable, Rarety, Inimitable, and Organized) in previous research objects has been proven to be able to be implemented and maintain the existence of traditional markets amid globalization. This research is a development of previous research with the addition of variable heritage tourism and technology in the traditional market managerial system. Researchers conducted a review and weighed that all research objects have great hopes in maintaining the existence of traditional markets. The concept of heritage tourism is part of traditional markets because traditional markets are a reflection of society and culture in an area. Apart from that, the existence of many traditional markets is more than 50 years old so it is not only a trade concept but also a cultural one. Meanwhile, the technology variable is included because currently, in the era of society 5.0, the role of technology is side by side with the role of traditional market players.